1989
DOI: 10.1346/ccmn.1989.0370512
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Palygorskite and Sepiolite Alteration as Deduced from Solid-State 27Al and 29Si Nuclear Magnetic Resonance Spectroscopy

Abstract: Abstract--The mechanisms of palygorskite and sepiolite alteration to smectite under mild hydrothermal conditions were investigated by solid-state 27A1 and 29Si magic-angle spinning-nuclear magnetic resonance (MAS-NMR) spectroscopy, X-ray powder diffraction (XRD) and transmission electron microscopy (TEM). Palygorskite altered to smectite in the presence of NaOH at 150"C. 27A1 MAS-NMR spectroscopy showed that the Al coordination changed from chiefly octahedral in palygorskite to chiefly tetrahedral in the smect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The addition of MgCO3 strongly increased the amount of Mg 2 § in solution and, consequently, favored the formation of saponite. Based on the XRD and NMR results, both Komarneni (1989) and Golden and Dixon (1990) concluded that a dissolution and reprecipitation mechanism was responsible for the saponite formation. Images obtained by TEM revealed that the newly formed saponite had a lath-like morphology similar to that of palygorskite.…”
Section: H E C T O R I T Ementioning
confidence: 99%
See 2 more Smart Citations
“…The addition of MgCO3 strongly increased the amount of Mg 2 § in solution and, consequently, favored the formation of saponite. Based on the XRD and NMR results, both Komarneni (1989) and Golden and Dixon (1990) concluded that a dissolution and reprecipitation mechanism was responsible for the saponite formation. Images obtained by TEM revealed that the newly formed saponite had a lath-like morphology similar to that of palygorskite.…”
Section: H E C T O R I T Ementioning
confidence: 99%
“…Images obtained by TEM revealed that the newly formed saponite had a lath-like morphology similar to that of palygorskite. Komarneni (1989) suggested a nucleation and epitaxial-growth mechanism for saponite on the surface of the palygorskite remnants. Hydrothermal experiments with sepiolite at 300~ and 300 bars in the presence of CsC1, MgC12, and CaC12 (Komarneni, 1989) revealed a similar dissolution and reprecipitation mechanism, but the nucleation and epitaxial-growth mechanism was absent; no explanation was given for this absence.…”
Section: H E C T O R I T Ementioning
confidence: 99%
See 1 more Smart Citation
“…Pyrophyllite dehydroxylate has been shown to have a well defined Al(5) environment from XRD and from the 14.1 T NMR speetrum, whieh was fitted to a quadrupolar lineshape [180] but field dependent simulations have pointed out some discrepancies [58]. Other systems studied include pyrophyllite [181], montrnorillonite [182], muscovite [183], imogolite [184,185], polygarskite/sepiofite [186] and laponite [187] have been reported. The transformation in the pillaring of clays has also been followed [188][189][190].…”
Section: Layer Alun~osiheatesmentioning
confidence: 99%
“…The undesirable cementing processes that would be produced seem to be inhibited by the transformation (reconstitution or dissolution-precipitation) under hydrothermal conditions of sepiolite into stevensite or saponite. This reaction has been documented previously by Güven & Carney (1979) and Komarneni et al (1989) using a solid:water (s:w) ratio of <1:1 at 3008C. This s:w ratio is far from the 1:20 excess water used in the preliminary study on the hydrothermal reactivity of the Madrid Basin saponitic clays.…”
mentioning
confidence: 55%